DEVELOPINNG A POP-UP BOOK AS MEDIA FOR TEACHING ENGLISH NUMBERS TO KINDERGARTEN STUDENTS - Andari, Syabila Poppi; Susilawati, Endang; Surmiyati, Surmiyati; Regina, Regina; Ikhsanudin, Ikhsanudin (English Education Department, 2023)
Procurement of teaching media to teach language is one of the teaching strategies to improve student's language skills, especially vocabulary knowledge. Students will be more engaged in learning if the media is adjusted to their needs. This research is development research. The purpose of this research was to develop a pop-up book of English numbers as teaching media for kindergarten students in Zonakata Kindergarten School. The writer used three phases of the ADDIE concept which are Analyze, Design, and Develop phases to develop the product in this research. The Analysis phase was done by interviewing with the teachers of Zonakata Kindergarten School to discover the teachers’ and students’ needs for developing the product and analyzed by using thematic analysis. The design phase was done by designing the content of the pop-up book based on the results of the analysis phase. The book consists of numbers from 1 to 10 with attractive pictures and pop-up techniques on it. The development phase was done by using the Canva application to design the content of the books and checked it towards the assessment rubric to create a better product. Based on the result of validation, the product has met the criteria to be used as teaching media by the teacher. By using this research product, the students attract to learn and easier to acquire English numbers.